Ideology, Institutions and Causes: the Committed Activist Life of a Durham Miner - Lewis Mates (Revue Française de Civilisation Britannique, 2017)
Drawing inspiration from Kevin Morgan’s recent study of trade unionist A.A. Purcell, this article analyses the activist commitment of Durham miner Henry Bolton; his changing ideology, and how this informed his political interventions in numerous contexts and through multifarious institutions and positions. Beginning his political journey as a Methodist and Liberal before converting to socialism, Bolton was particularly significant as a key example of a neglected but undoubtedly significant phenomenon; an influential left Labour Party activist whose politics were largely indistinguishable from that of Communists but who was only actually a party member (open or otherwise) for a very short period. Bolton’s causes were numerous and interlinking. Working through the union, Labour Party and local council he advanced the interests of the miners and their communities, controversially harnessing the resources of the council itself during the 1926 general strike and lockout (he remained under long-term police surveillance). A firm believer in working-class education, Bolton was a leading figure in the regional Labour college movement and founder of a Socialist Sunday School branch. The latter formed the nucleus for local conscientious objectors during the Great War. In the 1930s, Bolton used his positions in both the council and region-wide peace council to propagandise on foreign affairs, including supporting the Spanish Republic. Studying Bolton’s activist life throws considerable light on the complex and diverse political culture of the British left, richly demonstrating the vast number of different ways in which an activist could intervene in the political world, and the complexities of the ideologies on the Labour left.